2016
DOI: 10.1038/jhh.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and undiagnosed-hypertension in urban Chinese adults: a population-based cross-sectional study

Abstract: Hypertension is common in adults and often undiagnosed, and the prevalence of pre- and undiagnosed-hypertension remains unclear. We aimed to investigate the prevalence of pre- and undiagnosed-hypertension and their correlates among urban Chinese adults. A total of 7435 participants aged 20-79 were included in this study. Data on demographics, lifestyle and medical history were collected through a structured interview. Pre- and undiagnosed-hypertension was defined as systolic blood pressure/ diastolic blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
11
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
7
11
3
1
Order By: Relevance
“…The present study revealed that PP-HTN was 23.4% among slum adolescents of which proportion of undiagnosed cases was 16.03%, and data depict that huge mass of patients with undiagnosed hypertension still exists in the community and could be one of the important causes for high mortality and disability in India. A study conducted in China [7] accounted for undiagnosed hypertension was 12.3%; however, population-based study conducted in Kerala [8] and rural Sudan [9] shows that incidence of HTN was 23.6% and 38.2%, respectively, and results were much higher than present study and reason could be acculturation, emerging trend of western lifestyle and increased purchasing power as compared to population residing in slum area.…”
Section: Discussioncontrasting
confidence: 81%
“…The present study revealed that PP-HTN was 23.4% among slum adolescents of which proportion of undiagnosed cases was 16.03%, and data depict that huge mass of patients with undiagnosed hypertension still exists in the community and could be one of the important causes for high mortality and disability in India. A study conducted in China [7] accounted for undiagnosed hypertension was 12.3%; however, population-based study conducted in Kerala [8] and rural Sudan [9] shows that incidence of HTN was 23.6% and 38.2%, respectively, and results were much higher than present study and reason could be acculturation, emerging trend of western lifestyle and increased purchasing power as compared to population residing in slum area.…”
Section: Discussioncontrasting
confidence: 81%
“…Hikikomori, 43 sleep less than 6 hours, 44 decreased activity, 29 tobacco use and heavy alcohol consumption 23 Diet High in salt and fat, 45 soft drinks,chocolate or candies 1-6 times a week 23 Social and psychological factors Low life satisfaction,low social support and depressive symptoms, 23 prenatal life stress events, 46 the wealth gap,Lower education and a history of marital status 31 Other factors Wrist fracture,spina bifida, 47 a serum FT4 level increase of 1 ng/dl 49 A significant association between periodontal disease and hypertension instead of HN 48 WC -waist circumference, BMI -body mass index, FT4 -free thyroxine, more difficult to be diagnosed in young patients than in elderly patients. Therefore, in addition to effective interventions for diagnosed individuals, effective disease screening is necessary to improve prevention and awareness in potential HN patients.…”
Section: Lifestylementioning
confidence: 99%
“…For example, the incidence of HN was reported to be 55.3% in American football players 28 and 42.9% in police constables in a district of India, 22 both of which are higher than that in the general young population. Prehypertensive morbidity is also significantly increased in young adults who have low incomes, low social status, [29][30][31] and a family history of HN. 32 Risk factors for prehypertension.…”
mentioning
confidence: 99%
“…This increase in blood pressure has been associated with an elevated risk for the development of diseases such as hypertension and various cardiovascular accidents, including stroke, heart failure (HF), acute myocardial infarction (AMI), which have generated disabilities, limitations and premature death (BUNDY, HE, 2016, DEPALMA, HIMMELFARB, et al, 2018. The disease can be asymptomatic, especially in its early stages, and the symptoms are associated with chronic and / or severe cases (ZHANG, DENG, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%